Factors Influencing Indian Millennials’ Green Purchase Intention - Ragu Prasadh Rajendran, C. Joe Arun (International Journal of Advanced Science and Technology, 2020)
The research on millennials’ green intention is at a nascent stage in the Indian context. Though inconsistent results can be observed across the literature regarding the antecedent variables on youth intention of purchasing green products, analysing their impact on green intention will help in developing suitable strategies for green marketing. This research aims to find out the factors affecting the intention of young educated millennials in buying eco-friendly products. In this quantitative study, primary data was collected from 220 university students. The sample for questionnaires was based on non- probability sampling technique named convenience sampling. The present study aims to understand the influence of three independent variables such as environmental knowledge, environmental concern, and environmental attitude on green purchase intention of millennials. The findings of the study will assist in expediting the sluggish growth of green sector in India.